Enhanced thrombin generation and platelet binding on herpes simplex virus-infected endothelium. - Visser, M R (1988)
Atherosclerotic lesions have been reported to contain herpes simplex virus 1 (HSV-1) genomic material. This, and other previous evidence, suggests that latent viral infection may be an atherogenic trigger. Moreover, active HSV-1 lesions manifest marked fibrin deposition in microvessels. In this report we show that very early infection of human endothelial cells with HSV-1 appears to alter surface conformation as detected by merocyanine 540 staining. Concomitantly, the efficiency of prothrombinase complex assembly increases, resulting in a 2- to 3-fold accelerated rate of thrombin generation on the cell surface. Increased thrombin generation is probably doubly procoagulant, since we also demonstrate that thrombin-induced platelet accumulation on HSV-infected endothelium (50.7 +/- 9.3%) is increased compared to uninfected endothelium (9.5 +/- 2.1%; P less than 0.002). Associated with HSV infection, prostacyclin secretion in response to thrombin is diminished by a factor of 20, probably explaining the enhanced platelet attachment. We conclude that HSV infection shifts endothelial cell properties from anticoagulant to procoagulant, both by promoting prothrombinase complex formation and function and by increasing platelet binding, well before cell disruption takes place. Virus-induced changes in the endothelial plasma membrane and diminished prostacyclin secretion are suggested as the pathways for this pathophysiologic mechanism, which may be germane to atherosclerotic thrombosis as well as HSV-mediated tissue necrosis.